Visual detection of biofouling using hue-saturation-value (HSV) colour for ship hull cleaning robot - Nor Azman, Muhammad Ammar; Azian, Eiman Salleh; Zainal Abidin, Zulkifli; Mohd Yusoff, Marmeezee; Ibrahim, Ahmad Imran; Mohd Salim, Mohd Nazli; Abu Yamin, Muttaqqin (IET, 2022)
To achieve optimum fuel efficiency, ships typically undergo inspections and hull cleaning. Professional divers do the vast majority of the activities and services whilst having difficulties such as cloudy vision. Thus, having a visual detection that able to detect biofoulings is a good practice in determining biofouling location on ship surface. The project's objective is to create an automated object monitoring system to help robots with their work. By adapting Hue Saturation Value (HSV) colour model, detection of biofouling can be made via adjusting the colour scheme of an image. The studies' findings include tethered communication between multiple controllers and components, joystickcontrolled actuators operation, object recognition using the HSV colour model, and actuator behaviour in response to sensor input.